2013
DOI: 10.5012/bkcs.2013.34.7.2067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Treatment on Anatase TiO2Nanotube Arrays for Photoelectrochemical Water Splitting

Abstract: Hydrogen (H 2 ) treatment using a two-step TiO 2 nanotube (TONT) film was performed under various annealing temperatures from 350 ºC to 550 ºC and significantly influenced the extent of hydrogen treatment in the film. Compared with pure TONT films, the hydrogen-treated TONT (H:TONT) film showed substantial improvement of material features from structural, optical and electronic aspects. In particular, the extent of enhancement was remarkable with increasing annealing temperature. Light absorption by the H:TONT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Hydrogen, as a reducing atmosphere, can highly facilitate the gas diffusion into the titanium dioxide lattice structure and also prevents the solvent incorporation within the lattice . In this context, creating favorable defects in the material by annealing in reducing atmosphere, is another promising strategy to reinforce the performance of metal oxide photoanodes . Indeed, many hypotheses have confirmed that treating Ti‐based alloys in reducing atmospheres can considerably introduce oxygen vacancies with low formation energy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen, as a reducing atmosphere, can highly facilitate the gas diffusion into the titanium dioxide lattice structure and also prevents the solvent incorporation within the lattice . In this context, creating favorable defects in the material by annealing in reducing atmosphere, is another promising strategy to reinforce the performance of metal oxide photoanodes . Indeed, many hypotheses have confirmed that treating Ti‐based alloys in reducing atmospheres can considerably introduce oxygen vacancies with low formation energy .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, several studies reported the influence of hydrogen annealing on the activity of titania (TiO 2 : H) at high temperatures (350‐550 °C) for various durations. It was reported that annealing under hydrogen leads to the creation of defect states below the CB, thus reducing the band gap of TiO 2 and further extending its optical activity in the visible spectrum . Additionally, some reports have pointed out that hydrogen treatment could contribute to enhancing the photocurrent of the fabricated material due to its ability to passivate the surface defect states …”
Section: Introductionmentioning
confidence: 99%
“…24 Hydrogen-treatment can reduce metal oxide semiconductor materials by introducing oxygen vacancies and hydrogen impurities and thus is a simple method to increase the donor density and electrical conductivity. In recent years, several common photoanodes, TiO 2 , [25][26][27][28][29][30] α-Fe 2 O 3 , 31,32 WO 3 , 33 and BiVO 4 , 34,35 have been treated using this method and resulted in photocurrent density enhancement. By analogy, in this work, the annealed electrodeposited CuWO 4 films were further thermally treated under an atmosphere of 5% hydrogen in argon.…”
mentioning
confidence: 99%
“…From the Mott-Schottky plot, the slope of C sc -2 versus V gives the donor density. The donor density values are estimated from these plots and are found to be 1.2 9 10 18 and 1.8 9 10 17 cm -3 for S-TNT and TNT sample respectively [24]. The variation of donor density by an order of magnitude reflects the higher density of oxygen vacancy defects and corroborates the results of XPS, EPR and PL spectroscopy studies.…”
Section: Resultsmentioning
confidence: 70%